Equity Reform and High-Quality Development of State-Owned Enterprises: Evidence From China in the New Era - Liao, Hongwei; Wang, Dingqing; Zhu, Lei; Zhao, Jing (Frontiers in Psychology, 2022)
How to improve the development quality of state-owned enterprises is of great significance to the economic and social development in the transition period. And promoting the reform of mixed ownership is an important path for state-owned enterprises to achieve high-quality development. Based on the micro-data of China's A-share listed state-owned companies, the paper explores the impact of mixed ownership reform on the high-quality development of state-owned enterprises. It clarifies the importance and moderation of equity reform and the heterogeneity of impact effects from the theoretical mechanism analysis and empirical test. It also analyzes the reasons of inverted U-shape from the perspective of the transmission mechanism of the internal competition atmosphere and non-state-owned capital speculation motivation. It is found that the relationship between equity reform and state-owned enterprises’ high-quality development is inverted U-shaped with multi-dimensional heterogeneity. From the analysis of conduction mechanism, on the one hand, the equity reform can enhance the internal competitive atmosphere, stimulate the vitality of enterprises and improve the development quality for state-owned enterprises. On the other hand, it enhances the speculation motivation of enterprises and slows down the high-quality development process.